Encountering China: Early Modern European Responses - Rachana Sachdev; Li, Qinjun (Lexington Books, 2012)
Encountering China addresses the responses of early modern travelers to China who, awed by the wealth and sophistication of the society they encountered, attempted primarily to build bridges, to explore similarities, and to emulate the Chinese, though they were also critical of some local traditions and practices. Contributors engage critically with travelogues, treating them not just as occasional sources of historical information but as primary, literary texts deeply revelatory of the world they describe. Contributors reach back to the earliest European writings available on China in an effort to broaden and nuance our understanding of European contact with the Middle Kingdom in the early modern period. While the primary focus of these essays is the external gaze – European sources about China – contributors also tease out aspects of the Chinese world-view of the time, thus generating a conversation between Chinese literary and historical texts and European ones.